2021
DOI: 10.1111/1744-7917.12918
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile hormone regulates photoperiod‐mediated male reproductive diapause via the methoprene‐tolerant gene in the ladybeetle Harmonia axyridis

Abstract: Juvenile hormone (JH) absence induces photoperiod-mediated reproductive diapause, which is characterized by reproductive cessation. Although the role of methoprene-tolerant (Met)-mediated JH signaling in photoperiod-mediated female reproduction has been well documented, its role in male reproduction remains unclear. In this study, we investigated the role of JH in regulating photoperiod-mediated development of the male internal reproductive system (IRS) in the predatory ladybeetle Harmonia axyridis (Pallas). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 57 publications
(68 reference statements)
2
12
0
Order By: Relevance
“…[14][15][16][17][18][19][20] The reduction of JH titer triggers female reproductive diapause in Harmonia axyridis, 21 and JH regulates reproductive diapause via the methoprene-tolerant (Met) gene in male H. axyridis. 22 Similar results also have been found in female Colaphellus bowringi. 23 A 20E deficiency decreased ecdysis-triggering hormone signaling, reduced JH production, and induced diapause in C. bowringi.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…[14][15][16][17][18][19][20] The reduction of JH titer triggers female reproductive diapause in Harmonia axyridis, 21 and JH regulates reproductive diapause via the methoprene-tolerant (Met) gene in male H. axyridis. 22 Similar results also have been found in female Colaphellus bowringi. 23 A 20E deficiency decreased ecdysis-triggering hormone signaling, reduced JH production, and induced diapause in C. bowringi.…”
Section: Introductionsupporting
confidence: 79%
“…Many previous studies have revealed that juvenile hormone (JH) and 20E signaling pathways participate in the regulation of diapause 14–20 . The reduction of JH titer triggers female reproductive diapause in Harmonia axyridis , 21 and JH regulates reproductive diapause via the methoprene‐tolerant (Met) gene in male H. axyridis 22 . Similar results also have been found in female Colaphellus bowringi 23 .…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…4 Disruption of diapause can be induced in several ways, including by environmental cues, chemicals and hormonal stimuli. [5][6][7][8] The termination of diapause is the least understood part of the diapause process, 9 although it is an indispensable step for postdiapause development, ultimately playing a vital role in insect survival. For diapausing larvae, the synchronization of diapause termination with the developmental season is critical to successful pupal metamorphosis.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature and photoperiod were identified to induce facultative diapause in M. alternatus larvae 4 . Disruption of diapause can be induced in several ways, including by environmental cues, chemicals and hormonal stimuli 5–8 . The termination of diapause is the least understood part of the diapause process, 9 although it is an indispensable step for postdiapause development, ultimately playing a vital role in insect survival.…”
Section: Introductionmentioning
confidence: 99%